2022
DOI: 10.1002/cft2.20182
|View full text |Cite
|
Sign up to set email alerts
|

Water use and management practices on U.S. golf courses

Abstract: Measuring water use on U.S. golf courses is an essential component of measuring best management practice adoption. To provide timely and meaningful education regarding current water use, continued measurement of golf course water use is necessary. The objective of this study was to assess the current water use and related management practices on U.S. golf courses in 2020. A survey was developed and distributed electronically to 14,145 U.S. golf courses with 11% responding. Since the initial survey conducted in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 7 publications
0
9
0
Order By: Relevance
“…We postulate three primarily explanations for the reduction of winter overseeding. First, winter overseeding is resource intensive, especially with water and nutrients (Shaddox et al 2022(Shaddox et al , 2023b. Reductions in winter-overseeded area may be attributed to resource conservation practices, especially in the Southwest region where water supply constraints are prevalent (Shaddox et al 2022).…”
Section: Resultsmentioning
confidence: 99%
“…We postulate three primarily explanations for the reduction of winter overseeding. First, winter overseeding is resource intensive, especially with water and nutrients (Shaddox et al 2022(Shaddox et al , 2023b. Reductions in winter-overseeded area may be attributed to resource conservation practices, especially in the Southwest region where water supply constraints are prevalent (Shaddox et al 2022).…”
Section: Resultsmentioning
confidence: 99%
“…Total water applied per unit area as water applied to U.S. golf courses has declined by 25% between 2005 and 2022 (Shaddox et al., 2022). Sixty‐eight percent of survey respondents indicated they are keeping turfgrass dryer than in the past.…”
Section: Discussionmentioning
confidence: 99%
“…Sixty‐eight percent of survey respondents indicated they are keeping turfgrass dryer than in the past. Survey results suggested that using more drought tolerant turfgrasses is a significant factor in reduced water use and has become a central component of best management practices on golf courses (Shaddox et al., 2022).…”
Section: Discussionmentioning
confidence: 99%
“…However, irrigation is usually required to maintain successful turfgrass function in the many regions where turfgrasses are utilized, since rainfall normally cannot supply the amount of water necessary [2]. Water shortage is a continuing challenge for the turfgrass community due to increasing demands from urbanized population growth, coupled with increased drought incidence and seasonality of water availability [3][4][5][6]. Therefore, the development of management practices leading to water-efficient turfgrass landscapes is important across an expanding constituency.…”
Section: Introductionmentioning
confidence: 99%